Obesity, heart failure with preserved ejection fraction, and the role of glucagon‐like peptide‐1 receptor agonists - Giuliana Cimino; Muthiah Vaduganathan; Carlo M. Lombardi; Matteo Pagnesi; Enrico Vizzardi; Daniela Tomasoni; Marianna Adamo; Marco Metra; Riccardo M. Inciardi (ESC Heart Failure, 2024)
Abstract Heart failure with preserved ejection fraction (HFpEF) has a high prevalence, affecting more than 50% of patients with heart failure. HFpEF is associated with multiple comorbidities, and obesity is one of the most common. A distinct phenotype has been proposed for obese patients with HFpEF. Recent data show the beneficial role of glucagon‐like peptide‐1 receptor agonists (GLP‐1 RAs) for weight loss in diabetic and non‐diabetic patients with obesity or overweight when given as adjunctive therapy to diet and exercise. The mechanisms of action are related to paracrine and endocrine signalling pathways within the gastrointestinal tract, pancreas, and central nervous system that delay gastric emptying, decrease appetite, augment pancreatic beta‐cell insulin secretion, and suppress pancreatic glucagon release. These drugs are therefore potentially indicated for treatment of patients with HFpEF and obesity or overweight. Efficacy and safety need to be shown by clinical trials with a first one, Semaglutide Treatment Effect in People with obesity and heart failure with preserved ejection fraction (STEP HFpEF), recently concluded. The aim of the present review is to provide the pathophysiological and pharmacological rationale for GLP‐1 RA administration to obese patients with HFpEF.